Study on solubility and solubilisation of drying agent in supercritical carbon dioxide for improving local permeability of tight gas reservoir. (2nd January 2020) - Xiong, Yu; Fu, Xitong; Mo, Jun; Zhang, Liehui
Abstract : The AC component of drying agent described in literature 6 can be injected into tight gas reservoir formation to reduce original and residual water saturation caused by completion and stimulation. However, the pore and throat of formation in tight gas reservoir are so small that AC particles are difficult to be injected into them directly. Through experiments, we discovered that a certain amount of AC could dissolve in supercritical carbon dioxide (SCCO2 ) and it could separate out from SCCO2 when pressure decreased. Therefore, SCCO2 can be used as transport agent and bring it into tight gas reservoir for drying formation. We further study the solubility of AC in SCCO2 under different temperature and pressure, and also screen solubilizer to enhance the solubility in this paper. The results show that the solubility of AC in SCCO2 is 0.0005 mol/mol at 40°C and 8 MPa. When temperature is constant, the solubility of AC in SCCO2 increases with the increase of pressure, but the impact of temperature on the solubility shows different variation principle with pressure increasing. In addition, ethyl alcohol is the best solubilizer for increasing the solubility of AC in SCCO2, and the optimal concentration of solubilizer in SCCO2 is 10%. GRAPHICAL ABSTRACT: